2010
DOI: 10.1097/mcg.0b013e3181d04899
|View full text |Cite
|
Sign up to set email alerts
|

Is Endoscopic Mucosal Clipping Useful for Preventing Colonic Manometry Probe Displacement?

Abstract: Goal-To examine whether endoscopic mucosal clipping prevents probe migration.Background-Ambulatory colonic manometry can provide useful pathophysiologic information regarding colonic motor function. However, probe displacement during prolonged recording can be problematic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Also, gender,13,32 age,33 sleep pattern,11 stress,3,34 and differences in colonic contents may influence intrinsic activity of the colon 5. Extrinsic factors include sensor localization10,21 and migration,26,27 non-physiological conditions (sedation, prolonged immobilization, stressful laboratory environment, bowel preparation with complete evacuation of stool)16,17 and use of different instrumentation (solid-state manometers vs. perfused tube manometry) 8,9,12…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, gender,13,32 age,33 sleep pattern,11 stress,3,34 and differences in colonic contents may influence intrinsic activity of the colon 5. Extrinsic factors include sensor localization10,21 and migration,26,27 non-physiological conditions (sedation, prolonged immobilization, stressful laboratory environment, bowel preparation with complete evacuation of stool)16,17 and use of different instrumentation (solid-state manometers vs. perfused tube manometry) 8,9,12…”
Section: Discussionmentioning
confidence: 99%
“…Once the location of the probe was confirmed by fluoroscopy, the silk thread was released, freeing the probe. Subsequently, a clip-fixing device was introduced through the biopsy channel and the silk sutures located at the tip and at three other sites on the probe were clipped to the colonic mucosa) using mucosal clips (Olympus America Inc, Melville, NY) 26,27. The snare was removed.…”
Section: Methodsmentioning
confidence: 99%
“…Once the location was confirmed by fluoroscopy, the silk thread was released, freeing the probe. Next, the probe was clipped to the colonic mucosa using mucosal clips (Olympus America Inc, Melville, NY) . The probe was taped securely to the gluteal region.…”
Section: Methodsmentioning
confidence: 99%
“…). Clipping the catheter to the colonic mucosa minimizes the risk of becoming dislodged and migrating distally throughout the study . As colonoscopy in children is usually performed under general anesthesia, the potential effect of anesthesia on colon motility becomes significant.…”
Section: How To Perform the Test?mentioning
confidence: 99%
“…Clipping the catheter to the colonic mucosa minimizes the risk of becoming dislodged and migrating distally throughout the study. 21 As colonoscopy in children is usually performed under general anesthesia, the potential effect of anesthesia on colon motility becomes significant. It has been suggested that the study can be performed as early as 4 hours after recovering from anesthesia 22 but others have recently reported an important effect of anesthesia on colon motility and study interpretation when the study is performed on the same day of anesthesia.…”
Section: Catheter Placement and Sedationmentioning
confidence: 99%